2020
DOI: 10.24914/jeb.v23i2.3113
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan aplikasi nelayan pintar di Kabupaten Pati – Jawa Tengah

Abstract: Nelayan hidup dengan ketidakpastian karena mata pencahariannya yang berhubungan langsung dengan alam. Akibatnya, nelayan dituntut untuk dapat melakukan adaptasi dan mitigasi terhadap perubahan iklim yang dewasa ini terjadi sangat pesat. Inovasi TIK banyak dikembangkan untuk membantu nelayan dalam kegiatan melaut. Salah satu teknologi informasi yang dibuat dan dikembangkan oleh Kementerian Kelautan dan Perikanan untuk membantu kegiatan melaut nelayan adalah aplikasi Nelayan Pintar (Nelpin). Penelitian ini bertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…This mechanical gadget was created by the Oceanic Innovation Designing Studio (LPTK) of the Marine and Fisheries HR Exploration Organization, along with the Service of Correspondence and Informatics. The goal of the go-online fishermen program, also known as Smart Fishermen (Nepean), is to meet the various requirements of fishermen (Susilowati et al, 2020). Such as the weather, port conditions, wave size, wind direction, and prices in the fish market.…”
Section: Nelayan Pintarmentioning
confidence: 99%
“…This mechanical gadget was created by the Oceanic Innovation Designing Studio (LPTK) of the Marine and Fisheries HR Exploration Organization, along with the Service of Correspondence and Informatics. The goal of the go-online fishermen program, also known as Smart Fishermen (Nepean), is to meet the various requirements of fishermen (Susilowati et al, 2020). Such as the weather, port conditions, wave size, wind direction, and prices in the fish market.…”
Section: Nelayan Pintarmentioning
confidence: 99%
“…ti tools. Susilowati et al, (2020) also found about the perception of benefits to fishermen by using information and communication technology for fishing activities.…”
Section: Fishermen's Perception Of the Benefits Of Using Information And Communication Technologymentioning
confidence: 99%
“…The use of information and communication technology can not be separated from the role of the relevant stakeholders. (Susilowati et al, 2020) explained the role of stakeholders in increasing the use of information technology and information technology. (Nugroho et al, 2021) also explained how the role of stakeholders in overcoming the obstacles faced by fishermen in the use of information and communication technology.…”
Section: Stakeholder Role Strategy In Utilizing the Use Of Information And Communication Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Pengaruh penggunaan sistem informasi akuntansi terbukti mampu memberikan pengaruh untuk kinerja usaha kecil menengah sebesar 34,5% pada penelitian yang dilakukan oleh (Indralesmana & Suaryana, 2014) berjudul "Pengaruh Penerapan Sistem Informasi Akuntansi terhadap Kinerja Individu pada UKM di Nusa Penida". Penelitian yang berjudul "Pemanfaatan Aplikasi Nelayan Pintar di Kabupaten Pati, Jawa Tengah" yang dilakukan oleh (Susilowati, Thohir, SBM, & Suciati, 2020) juga menunjukkan bahwa aplikasi NelPin yang dibuat Kementerian Kelautan dan Perikanan ingin digunakan oleh para nelayan sangat bermanfaat untuk kegiatan melaut dan mudah untuk dioperasikan. Penggunaan sistem informasi akuntansi pada penelitian yang berjudul "Pengaruh Penerapan Sistem Informasi Akuntansi terhadap Kinerja Karyawan dengan Integritas Karyawan sebagai Variabel Pemoderasi" dilakukan oleh (Dita & Putra, 2016) di BPR Kabupaten Karangasem, menunjukkan bahwa penerapan sistem informasi akuntansi berpengaruh positif dan signifikan pada kinerja karyawan.…”
Section: Pendahuluanunclassified